On the Identity of Species of Oreobates (Anura: Craugastoridae) from Central South America, with the Description of a New Species from Bolivia - Pansonato, André; Motta, Ana [UNESP]; Cacciali, Pier; Haddad, Célio F. B. [UNESP]; Strüssmann, Christine; Jansen, Martin (Society for the Study of Amphibians and Reptiles, 2020)
The similar morphology of species in the genus Oreobates that inhabit rocky outcrops amidst the Seasonally Dry Tropical Forests and Cerrado savannas of central South America has led to taxonomic inaccuracies when only external morphology was considered. Therefore, researchers frequently fail to determine the true taxonomic status of some of these populations and thus attribute them to unidentified or misidentified species. Integrating different sources of data is of fundamental importance to understand the diversity of species in this group. Herein, we used external morphology (16 characters measured in 54 adult specimens), bioacoustics (238 advertisement calls of 19 specimens of Oreobates from six localities), and molecular evidence (based on 58 16S gene fragments representing 24 of the currently available names of Oreobates) to evaluate the taxonomic status and distribution range of Oreobates from 10 localities in central South America. We performed phylogenetic analysis, principal component analysis, and discriminant function analysis to evaluate the taxonomic status of Oreobates in central South America. We redescribe Oreobates heterodactylus based on a newly collected series of topotypes and additional material from other localities. We reassess the taxonomic status of Oreobates crepitans, herein considered as a junior synonym of O. heterodactylus. We also describe eastern Bolivian populations of Oreobates as a new species.